Effect of channel thickness on the field effect mobility of ZnO-TFT fabricated by sol gel process - Caglar, Yasemin; Caglar, Mujdat; Ilican, Saliha; Aksoy, Seval; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2015)
In this study, bottom-gate structured ZnO TFTs were fabricated on pSi/SiO2 substrate. ZnO active layers with different thickness were deposited by using sol gel spin coating method and the electrical performances of the obtained TFTs were investigated regarding the thickness of the channel layer. The effects of channel thickness on the structural and morphological properties of ZnO were examined. The mobility values of TFTs were significantly improved by increasing the thickness of active channel layer and the highest mobility of ZnO TFTs was obtained by 1.09 cm(2)/V s for 140 nm layer. ZnO TFTs showed a high off-current and this current increased as the channel thickness increased. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: ZnO-TFT; Sol gel spin coating; Field effect mobility